Critical Impediments Facing In-service Teachers during Distance Education: A Case of Kwame Nkrumah University in Zambia - Siame, Pethias; Hachintu, Joseph; Lubbungu, Jive (PT ARRUS Intelektual Indonesia, 2023)
This paper outlines the major impediments that in-service teachers undergoing distance education encounter at Kwame Nkrumah University. An impediment is a challenge, problem, or hindrance. The study used a qualitative approach, structured interviews, and document analysis methods. The marginal theory backed by tenets of equitable management underpinned the study. The study shows that in-service students are molested by their school managers when they need permission to attend residential schools. The students are bombarded with numerous responsibilities at their duty stations and hence fail to concentrate on their studies. In-service students have limited time to learn because residential schools are only conducted during the holidays for school-going children. Distance education learners depend on face-to-face learning. Other modes of learning such as Moodle are not favorable because most of the students come from rural areas where internet connectivity is a serious challenge. The study further reveals that in-service teachers are not considered for scholarships by the Higher Education Loans and Scholarships Board (HELSB) in Zambia. Due to financial constraints, some students drop out of school and withdraw from their studies while others delay completing their studies. Most in-service distance education students graduate while owing the institution which warrants their certificates to be withheld.